Modified delay-and-sum reconstruction algorithm to improve tangential resolution in photoacoustic tomography - Kalva, Sandeep Kumar (2018)
In photoacoustic/optoacoustic tomography (PAT/OAT) for a circular scanning geometry, the axial/radial resolution is not variant spatially and also do not depend on the ultrasound transducer (UST) aperture. But the tangential resolution is affected by the size of the detector aperture and is spatially variant. To counter this problem many techniques such as attaching a negative lens to the transducer surface, or using virtual detectors were proposed. However these techniques have difficulties. Therefore, a modified delay-and-sum reconstruction algorithm was proposed which can be used with the normal UST to improve the tangential resolution. In this work, we demonstrate the improvement of tangential resolution using the modified delay-and-sum reconstruction algorithm with experimental data. We have obtained more than twofold improvement of resolution in the tangential direction using non-focused and cylindrically focused USTs in a circular scanning geometry. We also observe that shape of the target object can also be preserved which is helpful for diagnosis and treatment purposes.